In‐person Interventions To Reduce Social Isolation And Loneliness: An Evidence And Gap Map - Vivian Welch; Elizabeth Tanjong Ghogomu; Sierra Dowling; Victoria I. Barbeau; Ali A. A. Al‐Zubaidi; Ella Beveridge; Mostafa Bondok; Payaam Desai; Rebecca Doyle; | Jimmy Huang; Tarannum Hussain; Alyssa Jearvis; et al. (Campbell Collaboration, 2024)
Indexed by WOS/Scopus/ERA